2007
DOI: 10.1097/mcd.0b013e3281c108d2
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and new polymorphic changes in the TCOF1 gene of patients with oculo–auriculo–vertebral spectrum and Treacher–Collins syndrome

Abstract: Oculo-auriculo-vertebral spectrum, the exact genetic predisposition of which has not yet been resolved, is characterized by varying degrees of the prevalently unilateral underdevelopment of craniofacial structures and spinal anomalies. Here, we analyzed four cases exhibiting multiple features of oculo-auriculo-vertebral spectrum and one case with Treacher-Collins syndrome. The cranium was analyzed using three-dimensional computed tomography, which reliably identifies craniofacial malformations. We detected one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Fischer et al (2006) found abnormal BAPX1 expression in a significant number of OAVS patients and suggested that epigenetic disregulation of BAPX1 might play a role in the etiology of OAVS. In addition, a few patients showing clinical overlap with OAVS had mutations in sal-like 1 (SALL1) (Kohlhase et al 1999;Keegan et al 2001;Kosaki et al 2007) or Treacher Collins-Franceschetti syndrome 1 (TCOF1) (Su et al 2007), the genes responsible for most cases of Townes-Brocks syndrome [OMIM 107480] and Treacher Collins syndrome [OMIM 154500], respectively, which are also associated with first and second branchial arch anomalies. Even though cytogenetic alterations have been associated with many cases of OAVS, most of the chromosomal aberrations are patient-specific, except that chromosome 5p (Choong et al 2003;Descartes 2006;Josifova et al 2004;Ala-Mello et al 2008) and 22q (Balci et al 2006;Xu et al 2008;Derbent et al 2003;Digilio et al 2009) have been implicated in a number of cases.…”
mentioning
confidence: 99%
“…Fischer et al (2006) found abnormal BAPX1 expression in a significant number of OAVS patients and suggested that epigenetic disregulation of BAPX1 might play a role in the etiology of OAVS. In addition, a few patients showing clinical overlap with OAVS had mutations in sal-like 1 (SALL1) (Kohlhase et al 1999;Keegan et al 2001;Kosaki et al 2007) or Treacher Collins-Franceschetti syndrome 1 (TCOF1) (Su et al 2007), the genes responsible for most cases of Townes-Brocks syndrome [OMIM 107480] and Treacher Collins syndrome [OMIM 154500], respectively, which are also associated with first and second branchial arch anomalies. Even though cytogenetic alterations have been associated with many cases of OAVS, most of the chromosomal aberrations are patient-specific, except that chromosome 5p (Choong et al 2003;Descartes 2006;Josifova et al 2004;Ala-Mello et al 2008) and 22q (Balci et al 2006;Xu et al 2008;Derbent et al 2003;Digilio et al 2009) have been implicated in a number of cases.…”
mentioning
confidence: 99%
“…Our finding of one of four HFM patients with a TCOF1 mutation (12) raised the possibility that TCOF1 mutations may play a role in a subset of patients with HFM. To test our hypothesis, we examined the genotype of the TCOF1 gene in 12 patients with HFM, and assessed the incidence of TCOF1 mutations with their characteristics.…”
mentioning
confidence: 72%
“…Multiple genes contribute to the wide phenotypic spectra of the first and second branchial arch syndromes that include facial asymmetries (6, 7, 10–12, 24–26) and family members with the same mutation can exhibit distinct penetrance of the phenotype (2). Here, 6 of 12 patients diagnosed with HFM exhibited a novel frameshift mutation c. 4127 ins G in exon 24 in the TCOF1 gene.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The child in the present report did not have any limb or vertebral defects but had pulmonary hypoplasia. The other genetic syndromes to be considered in the differential diagnosis are: Nager acrofacial dysostosis, Treacher Collins–Franceschetti syndrome, Townes–Brocks syndrome, Beckwith–Weidemann syndrome (BWS) and Russell–Silver syndrome (RSS) 6 – 9. Nager acrofacial dysostosis combines the facial anomalies of mandibulofacial dysostosis (Treacher Collins–Franceschetti) with hypoplastic/aplastic or triphalangeal thumbs.…”
Section: Discussionmentioning
confidence: 99%